The Effectiveness of Cognitive Behavioral Treatment for Adult Offenders: A Methodological, Quality-Based Review - Allen, Leana Cristine (International journal of offender therapy and comparative criminology, 2001)
Previous research on cognitive skills treatment programs has not included a comprehensive review of the effectiveness of these programs in reducing recidivism. This article reviews recent recidivism studies for two rehabilitation programs: Moral Reconation Therapy, which attempts to reduce recidivism by increasing the moral reasoning abilities of offenders, and Reasoning and Rehabilitation, which aims to educate offenders to change underlying criminogenic thoughts and attitudes. Using the Maryland Scale for Scientific Rigor, these studies were evaluated for their methodological strength and for the program's success in reducing the recidivism of offenders. In considering the findings and the strength of the methods for each program, this review concludes that Moral Reconation Therapy and Reasoning and Rehabilitation programs appear to be successful approaches to reducing recidivism